Antiviral Efficacy and Safety of Molnupiravir Against Omicron Variant Infection: A Randomized Controlled Clinical Trial - Rongrong Zou; Ling Peng; Dan Shu; Lei Zhao; Jianfeng Lan; Guoyu Tan; Jinghan Peng; Xiangyi Yang; Miaona Liu; Chenhui Zhang; Jing Yuan; Huxiang Wang; et al. (Frontiers Media S.A., 2022)
Background: The rapid worldwide spread of the Omicron variant of SARS-CoV-2 has unleashed a new wave of COVID-19 outbreaks. The efficacy of molnupiravir, an approved drug, is still unknown in patients infected with the Omicron variant.Objective: Evaluated the antiviral efficacy and safety of molnupiravir in patients infected with SARS-CoV-2 Omicron variant, with symptom duration within 5 days.Methods: We conducted a randomized, controlled trial involving patients with mild or moderate COVID-19. Patients were randomized to orally receive molnupiravir (800 mg) plus basic treatment or only basic treatment for 5 days (BID). The antiviral efficacy of the drug was evaluated using reverse transcriptase polymerase chain reaction.Results: Results showed that the time of viral RNA clearance (primary endpoint) was significantly decreased in the molnupiravir group (median, 9 days) compared to the control group (median, 10 days) (Log-Rank p = 0.0092). Of patients receiving molnupiravir, 18.42% achieved viral RNA clearance on day 5 of treatment, compared to the control group (0%) (p = 0.0092). On day 7, 40.79%, and 6.45% of patients in the molnupiravir and control groups, respectively, achieved viral RNA clearance (p = 0.0004). In addition, molnupiravir has a good safety profile, and no serious adverse events were reported.Conclusion: Molnupiravir significantly accelerated the SARS-CoV-2 Omicron RNA clearance in patients with COVID-19.Clinical Trial Registration: [chictr.org.cn], identifier [ChiCTR2200056817].